Critical commentary: the NSCA position statement on youth resistance training - Carpinelli, R. N. (Medicina Sportiva, 2012)
In an updated Position Statement on youth resistance training, the National Strength and Conditioning Association claimed that the Statement was based on a comprehensive analysis of the scientific evidence for resistance training in children. This Critical Commentary challenges that claim and reveals that their recommendations, especially the inclusion of the snatch and clean and jerk lifts, are without scientific foundation.